The Effectiveness of Giving Ginger Drink in Reducing Emesis Gravidarum in Pregnant Women (Case Study) - Tasripin, Mellysa Wulandari (CV. Literasi Publikasi Indonesia, 2024)
Pregnant mothers experience changes enhancement hormones progesterone, estrogen, and Human Chorionic Gonadotropin (hCG) so give rise to complaints of mother discomfort and nauseous vomiting in the first trimester, namely emesis gravidarum. This study was to know the effectiveness of drinking ginger to overcome nauseous vomiting. The respondents of study were 2 mothers given pregnancy therapy to drink ginger and not given ginger. Pregnant mothers were given 14 days to drink ginger warm and effective reduce nauseous vomit than no given therapy drink ginger. Drinking ginger is effective in overcoming nauseous vomiting in the mother's first trimester of pregnancy.